Estudio de la Metodología para la Elaboración de Cereales Expandidos con Cubierta Dulce (Honey Pop´s). - Olivarez Alajo, Maritza Jackeline (2018)
This research project was carried out in the canton of Latacunga, at Eloy Alfaro parish, in Salache Bajo neighborhood, at the Technical University of Cotopaxi, a degree in Agroindustrial Engineering, the Agave research laboratory and the Andean grains experimentation laboratory. Quantitative research on the Andean Grains Project and the Agave Project for Agroindustrial Purposes in the canton of Latacunga; The main objective of the research project was to experiment with three types cereals wheat (Tritricum aestivum), barley (Hordeum vulgare) and rye (Secale cereale) expanded at pressures between 75 and 100 PSI, after the expansion was placed a natural sweet cover honey base of panela and agave honey (Agave americana). The methodology applied in the development of the research was: experimental, exploratory and descriptive research; the deductive and analytical methods; descriptive, discriminative techniques, consumer analysis and survey types studies. Performing a survey of 20 students of the Agroindustrial Engineering career with two repetitions allowed us through a statistical analysis the determination of the best treatment resulting in the T2 consisting of WHEAT with PANEL cover at a pressure of 100 PSI, the use of a Sweet cover in expanded cereals will allow the product to be more attractive to the consumer. An analysis that was certified by LABOLAB Cia. Ltda determined nutritional, microbiological and useful life characteristics of T2, which allowed us to evaluate it as acceptable within the market, complying with the organoleptic, physical, chemical and microbiological parameters that a finished product needs.